A Magnetic Force Microscopy Study of Patterned T-Shaped Structures - Altbir-Drullinsky, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The study of patterned magnetic elements that can sustain more than one bit of the information is an important research line for developing new routes in magnetic storage and magnetic logic devices. Previous Monte Carlo studies of T-shaped magnetic nanostructures revealed the equilibrium and evolution of magnetic states that could be found as a result of the strong configurational anisotropy of these systems. In this work, for the first time, such behavior of T-shaped magnetic nanostructures is experimentally studied. In particular, T-shaped Co nanostructures have been produced by electron beam lithography using a single step lift-off process over Si substrates. The existence of four magnetic stable states has been proven by Magnetic Force Microscopy (MFM) and the analysis was complemented by Micromagnetic Simulations. The results confirmed that even for what can be considered large structures, with µm sizes, such four stable magnetic states can be achieved, and therefore two magnetic bits of information can be stored. We also addressed how to write and read those bits. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.